2021
DOI: 10.3390/ijms22115992
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy, Unfolded Protein Response, and Neuropilin-1 Cross-Talk in SARS-CoV-2 Infection: What Can Be Learned from Other Coronaviruses

Abstract: The COVID-19 pandemic is caused by the 2019–nCoV/SARS-CoV-2 virus. This severe acute respiratory syndrome is currently a global health emergency and needs much effort to generate an urgent practical treatment to reduce COVID-19 complications and mortality in humans. Viral infection activates various cellular responses in infected cells, including cellular stress responses such as unfolded protein response (UPR) and autophagy, following the inhibition of mTOR. Both UPR and autophagy mechanisms are involved in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 185 publications
(230 reference statements)
0
22
0
Order By: Relevance
“…These data suggest that SARS-CoV-2 Spike likely inhibits RIG-I activation of IFN-I at the level of the IRF3 transcription factor. In addition to eliciting an IFN-I antiviral response, virus infections can further cause replication stress resulting in the aggregation of unfolded and misfolded proteins in the endoplasmic reticulum (ER) and the triggering of the highly conserved unfolded protein response (UPR) pathway that governs cellular homeostasis ( Movaqar et al., 2021 ; Siri et al., 2021 ). While SARS-CoV-2 Spike blocked the IFN-I response, it instead potentiated the UPR as demonstrated via increased activation of the unfold protein response element as shown via luciferase reporter assays ( Figure 3G ).…”
Section: Resultsmentioning
confidence: 99%
“…These data suggest that SARS-CoV-2 Spike likely inhibits RIG-I activation of IFN-I at the level of the IRF3 transcription factor. In addition to eliciting an IFN-I antiviral response, virus infections can further cause replication stress resulting in the aggregation of unfolded and misfolded proteins in the endoplasmic reticulum (ER) and the triggering of the highly conserved unfolded protein response (UPR) pathway that governs cellular homeostasis ( Movaqar et al., 2021 ; Siri et al., 2021 ). While SARS-CoV-2 Spike blocked the IFN-I response, it instead potentiated the UPR as demonstrated via increased activation of the unfold protein response element as shown via luciferase reporter assays ( Figure 3G ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, some of the purple module hub-high traffic genes, such as MAPK1 ( 189 , 374 ), CUL2 ( 210 ), CMTM6 ( 162 ), TXNRD1 ( 375 ), RAB1A ( 376 ), DICER1 ( 377 ), RAB5A ( 209 ), HSP90B1 ( 343 ), MAGT1 ( 378 ), ADAM10 ( 379 , 380 ), SNX2 ( 89 ), OLA1 ( 381 ), SPTLC1 ( 382 ), SH3GLB1 ( 383 ), TIMM10B ( 384 ), and CREB1 ( 385 ) hub-high traffic TF, which are central for information exchange in this module, are potential targets for development of COVID-19 therapeutic strategies. Among these, the mitogen-activated protein kinase 1 ( MAPK1 ) hub-high traffic gene is a potential core target for many anti-COVID-19 therapeutic strategies ( 189 , 374 , 386 390 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, metformin help to reduce the release of inflammatory markers by affecting the MTOR and NF-kappa B pathways [39]. Previous studies have demonstrated that SARS-CoV-2 activates several cellular responses, including cellular stress responses such as unfolded protein response (UPR) and autophagy, through the inhibition of mTOR [40]. The biological mechanism of UPR and autophagy are involved in cellular and tissue homeostasis, apoptosis, and innate immunity modulation.…”
Section: Discussionmentioning
confidence: 99%